Truths and euphemisms: How euphemisms are used in the political arena - Savo Karam, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Politicians are notorious for their employment of words in a disguised fashion through the usage of euphemisms. Consequently, their message becomes a recurrent theme of conspicuous deception. Elected government representatives deliberately engage in grandiloquent expression conscious of its subversive capacity. The deviancy of euphemisms is guided by social norms that politicians are permitted to exercise in order to safeguard their images. When politicians envelop seemingly good intentions with conscious deception, people are harmed in the process. Those in power transgress justice and commit crimes with their overwhelming command of euphemisms. In fact, euphemisms are utilized as masks, hiding truths under the protective tones of a speaker with a genuine, worthwhile goal. Selective vocabulary is employed to arouse, rationalize and justify. To achieve this end, politicians misrepresent the facts of various political situations by using terms that completely transform or falsify them. Euphemisms are used simplistically in daily conversations. However, where they are used and misused more frequently is in the political arena, in such cases as “soft targets” or “peace keepers” or “collateral damage.” These expressions are heard frequently, while past ones are forgotten and new ones primed in their place as transgressions continue. In this paper, I will make use of Jurgen Habermas’ public sphere theory, a critical theory that demonstrates how the audience’s outlook affects political action. This article will demonstrate the deliberate use of euphemisms in political language both as a cultural element and as one that is constantly changing to suit the ever-changing political arena.